(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Azomethine compounds play a vital role in the treatment of various ailments including cancer. Computational methods are widely utilized for investigating the molecular effects and drug like properties of compounds. In this current research, novel amide-Schiff base hybrids were designed and evaluated for their potential against hepatocellular carcinoma. The mechanistic pathway and the prominent targets were identified using network pharmacology and enrichment analyses. This analysis merely showed that the designed compounds would be highly active against liver cancer by targeting the HSP90AA1, HSP90AB1 and GRB2 targets. The physicochemical, pharmacokinetic and toxicity parameters of the designed compounds were evaluated and the findings of these studies showed the druggable nature of the compounds. The molecular docking using MZ-Dock against the selected targets was performed, which was compared with the co-crystallized ligands and standards. All the tested compounds were exhibited better binding energy. Among them, the derivatives with furfuryl amine have a greater level of binding affinity against the tested targets. Thus, these derivatives can be effectively used in the management of liver cancer. However, biological studies are further warranted.